Basic Concepts of Islamic Economics: Purpose of Life, Islamic Economics and Islamic Economic Rationality - Maya Nur Cholida; Budi Jaya Putra (Yayasan Adra Karima Hubbi, 2024)
Islam Baground. Islamic economics is an economic system that explains all phenomena about choice behavior and decision making in every unit of economic activity or activity based on moral and ethical rules. This research discusses the basic concepts of Islamic economics which include the purpose of life, the principles of Islamic economics, and the rationality of Islamic economics in economic practice. The problem raised in this study is about how Islamic economics directs Muslims to achieve the welfare of the world and the hereafter through an approach that integrates spiritual and material dimensions. Purpose. The purpose of this research is to analyze how the purpose of life in Islam affects economic behavior and how Islamic economic rationality differs from the concept of conventional economic rationality. Method. The method used in this research is a qualitative literature study, by examining primary and secondary sources related to the concept of Islamic economics. Result. The results show that Islamic economics prioritizes the principles of justice, balance, and public good, where economic rationality is based on ethical considerations and ultimate goals that go beyond material gain alone. ic economics is an economic system that explains all phenomena about choice behavior and decision making in every unit of economic activity or activity based on moral and ethical rules. This paper explores the basic concepts of Islamic economics, focusing on the purpose of life, Islamic economic principles, and Islamic economic rationality. Islamic economics integrates moral and ethical dimensions derived from the Quran and Sunnah, promoting a balance between material and spiritual needs. The purpose of life in Islam emphasizes worship and servitude to Allah, which influences economic behaviors and decisions. Islamic economic principles advocate for justice, equity, and social welfare, guiding resource allocation, production, and distribution in a manner that prevents exploitation and ensures fairness. Islamic economic rationality extends beyond mere profit maximization, incorporating ethical considerations and long-term societal benefits. This holistic approach aligns individual and collective economic activities with broader spiritual and moral goals, fostering a sustainable and equitable economic system. Through this lens, the paper highlights how Islamic economics offers a comprehensive framework for addressing contemporary economic challenges.